Community and Local Self-Management in a Changing Situation at Present - Kotchapong, Sarayut; Bunmee, Boonchok; Rojanatrakut, Tanastha (Journal of MCU Buddhapanya Review, 2020)
The objective of this academic paper is to study the community and local self-management in the current situation. It was found that community and local self-management is a process of change for self-development of communities and locals. It also reduces the burden of the government to look after communities and localities. Which the self-management process of the local community There are 5 aspects of current management, which are 1) self-management of local communities, community plans 2) self-management of local communities in agriculture, 3) self-management of local communities in terms of natural resources and the environment 4) self-management of the local community in community finance and 5) self-management of the local community in the sufficiency economy Self-management in all 5 areas is an action in response to the current changes that affect life. It will also enable the people in the local community to have an independent idea of ​​self-management, which can lead to the process of public participation and the empowerment of people, groups, and organizations in the local community. Develop oneself towards goals those are strong and sustainable, self-reliant